Probiotic Ameliorate Gut Health and Growth Performance in Marwari Goat kids: A Substitute of Antibiotics - Pankaj Lavania; Kachhawaha, Subhash; Garbar Singh (Annals of Arid Zone, 2025)
Goat husbandry plays a vital role in providing house hold nutritional security, increased income and employment in rural transformation. In order to assess the influence of on-farm supplementary feeding of commercial probiotic on growth in growing kids has been evaluated. Twenty (3 months old) weaned kids of Marwari breeds were randomly divided into two groups of 10 each. One group served as control while the other as experimental group was fed probiotic @ 5 g kid-1d-1 for 90 days. Animals of both groups grazed on community pasture land. The results showed that probiotic supplemented experimental group gained significantly higher (P<0.05) body weight and improved average daily body weight gain by 18.55 g more than control group. The study further indicated that diahorrea and respiratory disorders occurred less frequently experimental group compared to control group animals. Conducting farmer’s participatory trial on farmer’s flock can prove to be a very effective approach for creating awareness and acceptance of technology..